Co-polarized and cross-polarized scattering of an off-axis focused Gaussian beam by a spherical particle. 1. Exact GLMT formalism. (December 2018) - Lock, James A.; Laven, Philip
Highlights: Calculated polarization-resolved scattering of an off-axis Gaussian beam by a homogeneous spherical particle. Found that cross-polarized scattering is nonzero if the off-axis beam is translated off-axis perpendicular to the scattering plane. Determined the wave theory reasons for the occurrence of non-zero cross-polarized scattering. Abstract: In static and dynamic light scattering, it has frequently been claimed that cross-polarized scattering cannot occur for single-scattering by a homogeneous spherical particle. Although this is true for both plane wave and on-axis Gaussian beam incidence, we show that cross-polarized scattering does occur when the beam is translated off-axis incidence perpendicular to the scattering plane. We find that the existence of cross-polarized scattering is a direct result of the breaking of the circular symmetry of the beam with respect to the center of the particle when the beam is translated off-axis in wave theory, and to the constraint of the incident beam being a solution of Maxwell's equations.